Genotypic differences for water-use efficiency and weed competitiveness in dry direct-seeded rice - Mahajan, G.; Ramesha, M.S.; Chauhan, B.S. (Wiley, 2015)
Genotypes with improved weed competitiveness and water‐use efficiency (WUE) are needed to enhance and sustain productivity in dry direct‐seeded rice (DDSR) (Oryza sativaL.). The objective of this study was to investigate the relative performance of selected genotypes under DDSR for yield, WUE, and weed‐inflicted relative yield losses in the rainy seasons of 2012 and 2013. Six rice genotypes (two hybrids [US‐323 and PAC‐837], two cultivars [PR‐115 and PR‐120], and two advanced breeding lines [CR‐2703 and CR‐2706]) were grown in a split‐split‐plot arrangement in a randomized complete block, with soil water potential (10 kPa, well watered; and 20 kPa, stressed) as main plots, weed infestation levels (weed free and partially weedy) as subplots, and genotypes as sub‐subplots. Relative grain yield loss among genotypes attributable to water stress had a range of 24–47%; it was lowest for PAC‐837 (4.96 and 6.5 Mg ha−1at 10 and 20 kPa, respectively) and highest for PR‐120 (3.91–7.37 Mg ha−1at 10 and 20 kPa, respectively). Similarly, weed‐inflicted relative grain yield loss (partially weedy vs. weed free) among genotypes had a range of 10 to 47%; it was lowest for PAC‐837 (5.42–6.04 Mg ha−1) and highest for US‐323 (3.10–5.91 Mg ha−1). Weeds reduced WUE in all genotypes (12–46%) except PAC‐837. Under weed‐free conditions, PR‐120 had the highest yield (6.99 Mg ha−1) and WUE (0.52 kg m−3). This study suggested that high yield potential and improved weed‐suppressive ability were compatible, and therefore breeding for both traits should lead to strengthened integrated crop management strategies in DDSR.